Radiance energy losses calculation for low-temperature air plasma with the additions of alkaline metals; Korus 2001; Vol. 1 - Vlasov V. A. Viktor Alekseevich (2001, 2001)
During the study of processes that take place in low-temperature plasma it is necessary to determine different parameters of the plasma system. One of the relevant parameters is the energy of system. The energy of the system can be spent by various methods. One of them is the energy radiance. This paper dedicated to modeling of parameters of a low-temperature plasma with various additions of alkaline metals